2009
DOI: 10.1128/jb.00417-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Repair and Damage Tolerance Mechanisms for DNA-Protein Cross-Links in Escherichia coli

Abstract: DNA-protein cross-links (DPCs) are unique among DNA lesions in their unusually bulky nature. We have recently shown that nucleotide excision repair (NER) and RecBCD-dependent homologous recombination (HR) collaboratively alleviate the lethal effect of DPCs in Escherichia coli. In this study, to gain further insight into the damage-processing mechanism for DPCs, we assessed the sensitivities of a panel of repair-deficient E. coli mutants to DPC-inducing agents, including formaldehyde (FA) and 5-azacytidine (aza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
51
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 78 publications
7
51
2
Order By: Relevance
“…The dissociation of stalled DnaB from DNA observed in the present study accounts at least in part for the inactivation of the replisome in vitro, although the in vitro half-lives of stalled replisome (4 -6 min) and DnaB (36 min) differ considerably. The inactivation of the replisome due to loss of DnaB also seems to be consistent with the observations that reactivation of stalled replication fork requires reloading of DnaB (or replication machinery) via the PriA helicase in E. coli (57) and that the priA mutant is hypersensitive to DPC-inducing agents (58). However, further studies are necessary to account for the discrepancy between the in vitro and in vivo stabilities of roadblocked E. coli replisomes (see also below).…”
Section: Discussionsupporting
confidence: 57%
“…The dissociation of stalled DnaB from DNA observed in the present study accounts at least in part for the inactivation of the replisome in vitro, although the in vitro half-lives of stalled replisome (4 -6 min) and DnaB (36 min) differ considerably. The inactivation of the replisome due to loss of DnaB also seems to be consistent with the observations that reactivation of stalled replication fork requires reloading of DnaB (or replication machinery) via the PriA helicase in E. coli (57) and that the priA mutant is hypersensitive to DPC-inducing agents (58). However, further studies are necessary to account for the discrepancy between the in vitro and in vivo stabilities of roadblocked E. coli replisomes (see also below).…”
Section: Discussionsupporting
confidence: 57%
“…(concentration of formaldehyde causing 90% cell death) of ϳ5 mM formaldehyde, a result that is consistent with a previous study done in a different strain background (45). These data confirm that UvrD is critical for limiting DPC-induced cytotoxicity.…”
Section: Resultssupporting
confidence: 81%
“…Two independent studies (37,45) have also demonstrated that uvrA mutants are sensitive to formaldehyde. One of these studies examined the formaldehyde sensitivity of both ⌬uvrD and ⌬uvrA strains, but these strains were generated from two different parental backgrounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian cells the upper size limit of crosslinked proteins (CLPs) amenable to NER is around 8 kDa, eliminating the role of NER in the repair of DPCs in vivo (9). DPCs not amenable to NER are processed by homologous recombination in bacterial and mammalian cells (2,7,9,10). These data clearly demonstrate that DPCs impose steric hindrances on DNA polymerases and NER factors, impairing replication and repair.…”
mentioning
confidence: 96%